Dexmedetomidine may upregulate the expression of caveolin-1 in lung tissues of rats with sepsis and improve the short-term outcome - Zhang, Yun; Ran, Ke; Zhang, Shu-Bin; Jiang, Lili; Wang, Dan; Li, Zhi-Jian (Molecular medicine reports, 2017)
Dexmedetomidine (DXM) is a selective α2-adrenoceptor (α2-AR) and imidazoline receptor (IR) agonist that has been reported to regulate inflammatory responses mediated by diverse signaling pathways through α2-AR. The majority of the reported receptors or downstream molecules have been demonstrated to locate with caveolin-1, a protein suggested to participate in regulating Toll-like receptor 4 (TLR4)-mediated inflammatory responses and the pathogen endocytosis capability of macrophages. The present study hypothesized that DXM may influence these pathways by regulating the expression of caveolin-1 and mediating the subsequent effects. Using a cecal-ligation and puncture-induced rat sepsis model, it was initially observed that pre-emptive DXM is able to upregulate and stabilize the amount of caveolin-1 expression, which may be partly antagonized by both α2-AR and the IR antagonist atepamezole (APZ). The pathophysiological parameters indicated that DXM is able to inhibit secondary lung injury, in addition to the rise of body temperature and arterial lactate accumulation, however it marginally increased arterial glucose and the murine sepsis score, which can be largely antagonized by APZ. The overall effect was beneficial and improved the 24-h cumulative survival rate of rats with sepsis. In conclusion, preemptive clinical sedative doses of DXM may upregulate the expression of caveolin-1 downregulated by sepsis, which may contribute to the inhibition of inflammatory pathways such as TLR4-mediated pathways. Furthermore, DXM may favor the improvement of short-term outcomes by the regulation of other metabolic pathways.